2012
DOI: 10.1177/0093854812437022
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Substance Use and Aggression

Abstract: Substance use disorders (SUDs) in youth are strongly associated with aggression, delinquency, and involvement with the juvenile justice and mental health systems. This article reviews the relationship between aggression and SUDs and discusses evidence-based approaches to assessment and intervention, with a focus on youth in secure settings. While evidence indicates etiological overlap, SUDs also confer risk for aggression and delinquent behavior. SUDs and aggression are each influenced by executive functions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 185 publications
(219 reference statements)
1
39
0
2
Order By: Relevance
“…The link between substance abuse and adolescent aggressive behaviours has also been established, and adolescent substance abuse has been identified as a risk factor for delinquency and aggression (Doran et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The link between substance abuse and adolescent aggressive behaviours has also been established, and adolescent substance abuse has been identified as a risk factor for delinquency and aggression (Doran et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Aggressive behaviours are also commonly mentioned by parents, who experience victimization and intimidation from the adolescent, often as a means to obtain money to support their habits (Abrahams 2009;Jackson et al 2007;Thesnaar 2011). The link between substance abuse and adolescent aggressive behaviours has also been established, and adolescent substance abuse has been identified as a risk factor for delinquency and aggression (Doran et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Considering juvenile justice outcomes generally, some argue that all treatments are equally effective (Lipsey, 2009). Others suggest that type of treatment is important and specifically suggest that family-based treatments produce better results than individual or group interventions (Chassin et al, 2009; Doran, Luczak, Bekman, Koutsenok, & Brown, 2012). Undoubtedly, more research on juvenile drug courts is needed, particularly on the importance of the nature of treatment provided and the involvement of families (Cooper, 2009; Wilson, Mitchell, & MacKenzie, 2006).…”
mentioning
confidence: 99%
“…For instance, studies in Nigeria (among students) and in Ghana (among homeless youth) found that alcohol and substance use is associated with an increased likelihood of risky sexual behavior, with accompanied increased risk for sexually transmitted infections including HIV (Nwagu, 2016;Oppong et al, 2014). While circumstances on the street may render children and youth vulnerable to various kinds of psychological problems and health risks (Burns, Daileader, & Finger, 2004), street children using drugs and psychoactive substances are more likely to engage in crime and interpersonal violence and are also more likely to suffer traffic accidents (Doran, Luczak, Bekman, Koutsenok, & Brown, 2012).…”
Section: Substance Use Disorders Among Young People In Wcamentioning
confidence: 99%